Bis[μ-4-hydroxy-N′-(4-methoxy-2-oxidobenzylidene)benzohydrazidato]bis[pyridinecopper(II)] - Lair, Nooraziah Mohd; Khaledi, Hamid; Ali, Hapipah Mohd; Puteh, Rustam (International Union of Crystallography, 2010)
In the title compound, [Cu2(C15H12N2O4)2(C6H5N)2], each CuII atom is chelated by the tridentate doubly deprotonated Schiff base and a pyridine molecule in a nearly planar environment (r.m.s. deviation for all non-H atoms = 0.107 Å). The metal ions are bridged by one O atom from the symmetry-related Schiff base ligands, forming a centrosymmetric dinuclear copper(II) complex. The dimeric complex is linked to another dimer via weaker Cu-O interactions and also O-H...N hydrogen bonds.